Structurally distinct nicotine immunogens elicit antibodies with non-overlapping specificities - Pravetoni, M (2011)
Nicotine conjugate vaccine efficacy is limited by the concentration of nicotine-specific antibodies that can be reliably generated in serum. Previous studies suggest that the concurrent use of 2 structurally distinct nicotine immunogens in rats can generate additive antibody responses by stimulating distinct B cell populations. In the current study we investigated whether it is possible to identify a third immunologically distinct nicotine immunogen. The new 1′-SNic immunogen (2S)-N,N′-(disulfanediyldiethane-2,1-diyl)bis[4-(2-pyridin-3-ylpyrrolidin-1-yl)butanamide] conjugated to keyhole limpet hemocyanin (KLH) differed from the existing immunogens 3′-AmNic-rEPA and 6-CMUNic-BSA in linker position, linker composition, conjugation chemistry, and carrier protein. Vaccination of rats with 1′-SNic-KLH elicited high concentrations of high affinity nicotine-specific antibodies. The antibodies produced in response to 1′-SNic-KLH did not appreciably cross-react in ELISA with either 3′-AmNic-rEPA or 6-CMUNic-BSA or vice-versa, showing that the B cell populations activated by each of these nicotine immunogens were non-overlapping and distinct. Nicotine retention in serum was increased and nicotine distribution to brain substantially reduced in rats vaccinated with 1′-SNic-KLH compared to controls. Effects of 1′-SNic-KLH on nicotine distribution were comparable to those of 3′-AmNic-rEPA which has progressed to late stage clinical trials as an adjunct to smoking cessation. These data show that it is possible to design multiple immunogens from a small molecule such as nicotine which elicit independent immune responses. This approach could be applicable to other addiction vaccines or small molecule targets as well.